Scoping study: Capacities and needs for strengthening water-energy-food-environment (WEFE) nexus approaches in Nepal - Buchy, Marlène; Shrestha, Sajani; Shrestha, Gitta (International Water Management Institute, 2022)
This report presents the results of a scoping study conducted between April and June 2022 in Nepal as part of the CGIAR NEXUS Gains Initiative. The study aims to inform and offer a baseline for the development of a water - energy - food - environment (WEFE) nexus capacity strengthening strategy for the Initiative in Nepal, which will serve as a hub for NEXUS Gains capacity strengthening activities in the sub-region. The study sheds light on the current status of capacities to develop and implement nexus solutions among key Nepali actors in the water, energy, forestry, biodiversity and agriculture sectors, and on the enabling environment for pursuing such integrated solutions. The assessment draws attention to equity and inclusion as critical dimensions of WEFE nexus approaches, and identifies constraints and strategies to strengthen the capacities, leadership, and influence of women WEFE actors.